A study on customers satisfaction level on services provided by Sabah Ports Sdn. Bhd. / Rozanizah Said - Said, Rozanizah (2008)
Sabah Ports Sdn. Bhd. is a company that focusing mainly on manpower development and training, streamlining the port operations, acquisition of new and modern cargo handling equipment, and planning and undertaking new cargo handling facilities. The company provides various facilities to the customers such as berth facilities, cargo and container handling facilities, labour provision and storage facilities. The purpose of this study is to identify the customers' satisfaction level on services provided by Sabah Ports Sdn. Bhd. This study was conducted at Kota Kinabalu and Sapangar area only. The approach used for this study in getting information is through the use of self administered questionnaire. Data that have been collected is then processed with the use of SPSS. Information obtained is then turned into charts and tables so that it can be evaluated and explained easily. Based on the findings, most of the respondents are satisfied with the services provided by Sabah Ports Sdn. Bhd. However, only few of the respondents gave their suggestions in improving the services provided by the company.